Association of germline variation with the survival of women with BRCA1/2 pathogenic variants and breast cancer - Taru A. Muranen; Sofia Khan; Rainer Fagerholm; Kristiina Aittomäki; Julie M. Cunningham; Joe Dennis; Goska Leslie; Lesley McGuffog; Michael T. Parsons; Jacques Simard; Susan Slager; Penny Soucy; et al. (NATURE PUBLISHING GROUP, 2022)
Germline genetic variation has been suggested to influence the survival of breast cancer patients independently of tumor pathology. We have studied survival associations of genetic variants in two etiologically unique groups of breast cancer patients, the carriers of germline pathogenic variants in BRCA1 or BRCA2 genes. We found that rs57025206 was significantly associated with the overall survival, predicting higher mortality of BRCA1 carrier patients with estrogen receptor-negative breast cancer, with a hazard ratio 4.37 (95% confidence interval 3.03-6.30, P=3.1x10(-9)). Multivariable analysis adjusted for tumor characteristics suggested that rs57025206 was an independent survival marker. In addition, our exploratory analyses suggest that the associations between genetic variants and breast cancer patient survival may depend on tumor biological subgroup and clinical patient characteristics.